PROFESSIONAL AND SOCIAL ACTIVATION OF RURAL POPULATION IN POLAND – STRUCTURAL ASPECTS AND LEGAL FRAMEWORKS - Jakub GOŁAŚ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The main aim of the article was to characterise the issue of professional and social activation of rural population in Poland from two crucial perspectives: of the structure of employment activities of rural population and of the set of legal measures designed to implement and assure desired levels of working activity of domestic rural population. The structural study focuses mainly on such aspects as a number of employed persons in agriculture, hunting and forestry with an indication of such issues as employment in crop and animal production and hunting, employment in agriculture, different status of employees or total number of registered unemployed persons living in rural area. In terms of structural aspects, it should be firstly noted that statistical data clearly shows that employment in agriculture in private farms is the most common form of employment of rural population. It should be also highlighted that the employer or own-account worker on private farm were the most common employment status for rural population in Poland. In terms of legal aspects, the study mainly focuses on analysis of complex legal provisions of both community and domestic law. The Regulation (EU) No 1305/2013 defines basic and fundamental principles of the Common Agriculture Policy related to the issue of professional and social activation of rural population, while domestic acts intend to define legal frameworks customised to Polish realities.